1 Records of the Governor and Company of the Massachusetts Bay 85 (1853) - (:unkn) unknown (My University, 1631)
"Further, it is ordered, that noe pson shall travell single betwixte theis plantacons & Plymouthe, nor without some armes, though 2 or 3 togeather."
Keywords: REQUIRED POSSESSION